Determinants of Long Immunization Clinic Wait Times in a Sub-Saharan African Country. (June 2021) - Ekhaguere, Osayame Austine; Oluwafemi, Rosena Olubanke; Oyo-Ita, Angela; Mamlin, Burke; Bondich, Paul; Mendonca, Eneida A.; Rollins, Angela L.
The wait time clients spend during immunization clinic visits in low- and middle-income countries is a not well-understood reported barrier to vaccine completion. We used a prospective, observational design to document the total time from client arrival-to-discharge and all sequential provider-client activities in 1 urban, semi-urban, and rural immunization clinic in Nigeria. We also conducted caregiver and provider focus group discussions to identify perceived determinants of long clinic wait times. Our findings show that the time from arrival-to-discharge varied significantly by the clinic and ranged between 57 and 235 minutes, as did arrival-to-all providers-client activities. Focus group data attributed workflow delays to clinic staff waiting for a critical mass of clients to arrive for their immunization appointment before starting the essential health education talk or opening specific vaccine vials. Additionally, respondents indicated that complex documentation processes caused system delays. Research on clinic workflow transformation and simplification of immunization documentation is needed.